Compudose® compared with Synovex-H® for finishing yearling heifers - Laudert, S.B. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Feedlot heifers implanted once with either Compudose® or Synovex-H® performed similarly, with daily gains of 3.16 vs 3.27 lbs, respectively. Compudose retention in the ear was 97.5%. Implant site abscess rate was 2.5% for Compudose and 13.7% for Synovex-H.
Keywords: Beef; Compudose®; Synovex-H®; Yearling heifers